Belize. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Belize during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as public policies, technology, laboratories, rural development, agricultural health, resilience against climate change, animal health and in the export of cattle. Likewise, work was done on antimicrobial resistance, backyard gardening, in vitro insemination and geographic information systems. Finally, the value chains of sugar, poultry, ruminants and local egg production were supported.